2020
DOI: 10.3390/pathogens9030215
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Application of a Bacteriophage Infecting the Fish Pathogen Aeromonas hydrophila

Abstract: Bacteriophages are increasingly being used as biological control agents against pathogenic bacteria. In the present study, we isolate and characterize bacteriophage Akh-2 from Geoje Island, South Korea, to evaluate its utility in controlling motile Aeromonas septicemia. Akh-2 lysed four of the seven Aeromonas hydrophila strains tested. Transmission electron microscopy analysis showed that Akh-2 belongs to the Siphoviridae family, with head and tail sizes of 50 ± 5 and 170 ± 5 nm, respectively. One-step growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…The lytic ability of ΦECP8 and ΦECP9 was not affected within a temperature range of 25-55°C, the infectivity of Aeromonas hydrophila phages ΦZH1 and ΦZH2 were highly sensitive to a temperature above 40°C (El-Araby et al, 2016) but in our results, the thermal stability of phage ΦAHP7 was sensitive to elevated temperature (55ºC to 70ºC) (Chen et al, 2018). In the same context, Akmal et al (2020) reported that Aeromonas phage Akh-2 retained its infectivity from -80°C to 37°C after three days of incubation.…”
Section: Application Of Bacteriophages In Artificially Contaminated Fsupporting
confidence: 41%
See 1 more Smart Citation
“…The lytic ability of ΦECP8 and ΦECP9 was not affected within a temperature range of 25-55°C, the infectivity of Aeromonas hydrophila phages ΦZH1 and ΦZH2 were highly sensitive to a temperature above 40°C (El-Araby et al, 2016) but in our results, the thermal stability of phage ΦAHP7 was sensitive to elevated temperature (55ºC to 70ºC) (Chen et al, 2018). In the same context, Akmal et al (2020) reported that Aeromonas phage Akh-2 retained its infectivity from -80°C to 37°C after three days of incubation.…”
Section: Application Of Bacteriophages In Artificially Contaminated Fsupporting
confidence: 41%
“…ΦZH1 and ΦZH2 were classified in the family Podoviridae with strong virulence against Aeromonas hydrophila infecting Nile tilapia (El-Araby et al, 2016). Recently, Aeromonas phage Akh-2 was molecularly characterized and classified in the Siphoviridae family, phage Akh-2 was used as a therapy against Aeromonas infections in fish (Akmal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Phage treatment also proved effective against a variety of additional fish pathogens, with the administration by intramuscular injection of phages Φ2, and Φ5 (Myoviridae) achieving up to 100% survival in catfish (Pangasianodon hypophthalmus) infected with Motile Aeromonas Septicemia (MAS), caused by A. hydrophila; the survival rate was 18.3% in untreated fish [118]. A similar remarkable protective effect was achieved with the PAS-1 phage when used to combat the furunculosis caused by A. salmonicida in Rainbow trout (Oncorhynchus mykiss) [119]. In in vitro studies, the use of effective phage cocktails (AS-A, AS-D, AS-E) against this pathogen showed a faster control of bacterial concentration as well as a decrease in the frequency of occurrence of phage-resistant mutants.…”
Section: Aquaculturementioning
confidence: 86%
“…Infected (1 × 10 7 cfu/mL) loah treated by immersion in water containing 1.0 × 10 8 pfu/mL of single phage preparation Mortality rates were 16%, 53%, 57%, and 56.67% after 24, 48, 72, 96 h respectively when compared to the control group with 100% mortality; most of the surviving fish showed no disease symptoms [112] (2020) The maximum reduction in mortality varied from 29% to 92% for turbot and from 49% to 86% for Atlantic cod assessed during the experiment and depending on the strain used; notably, reduction in mortality was not significant in the majority of cases at the end of the experiment [113] Infected Senegalese sole juveniles were treated with single phage preparation After 72 h, infected fish juveniles treated with phages showed no mortality contrary to 36% mortality in the control group [101] (2016)…”
Section: Phage Application In Fish and Seafood Industry In Practicementioning
confidence: 98%